Decompressive craniectomy in head injury - Abrar A Wani; Tanveer I Dar; Altaf U Ramzan; Nayil K Malik; Altaf R Kirmani; AR Bhatt; SS Chhibber; Shaikh Javaid; MA Wani (The Indian Journal of Neurotrauma, 2009)
Decompressive craniectomy has been used to treat severe intracranial hypertension secondary to various causes like trauma, cerebral infarction, subarachnoid hemorrhage, and spontaneous hemorrhage, refractory to medical treatment. There are many different approaches grouped under the term ‘decompressive craniectomy’ with all of them aiming at reduction of raised intracranial pressure. We have reviewed the literature and tried to describe the mechanism, various types, indications and complications of this procedure.